Diverse Molecular Mechanisms Underlying Microbe-Inducing Male Killing in the Moth Homona magnanima - Arai, Hiroshi; Takamatsu, Takumi; Lin, Shiou-Ruei; Mizutani, Tetsuya; Omatsu, Tsutomu; Katayama, Yukie; Nakai, Madoka; Kunimi, Yasuhisa; Inoue, Maki N. (Applied and environmental microbiology, 2023)
Many microbes induce male killing (MK) in various insect species. However, it is not well understood whether microbes adopt similar or different MK mechanisms. Male killing (MK) is a type of reproductive manipulation induced by microbes, where sons of infected mothers are killed during development. MK is a strategy that enhances the fitness of the microbes, and the underlying mechanisms and the process of their evolution have attracted substantial attention. Homona magnanima , a moth, harbors two embryonic MK bacteria, namely, Wolbachia ( Alphaproteobacteria ) and Spiroplasma ( Mollicutes ), and a larval MK virus, Osugoroshi virus (OGV; Partitiviridae). However, whether the three distantly related male killers employ similar or different mechanisms to accomplish MK remains unknown. Here, we clarified the differential effects of the three male killers on the sex-determination cascades and development of H. magnanima males. Reverse transcription-PCR demonstrated that Wolbachia and Spiroplasma , but not OGVs, disrupted the sex-determination cascade of males by inducing female-type splice variants of doublesex ( dsx ), a downstream regulator of the sex-determining gene cascade. We also found that MK microbes altered host transcriptomes in different manners; Wolbachia impaired the host dosage compensation system, whereas Spiroplasma and OGVs did not. Moreover, Wolbachia and Spiroplasma , but not OGVs, triggered abnormal apoptosis in male embryos. These findings suggest that distantly related microbes employ distinct machineries to kill males of the identical host species, which would be the outcome of the convergent evolution. IMPORTANCE Many microbes induce male killing (MK) in various insect species. However, it is not well understood whether microbes adopt similar or different MK mechanisms. This gap in our knowledge is partly because different insect models have been examined for each MK microbe. Here, we compared three taxonomically distinct male killers (i.e., Wolbachia , Spiroplasma , and a partiti-like virus) that infect the same host. We provided evidence that microbes can cause MK through distinct mechanisms that differ in the expression of genes involved in sex determination, dosage compensation, and apoptosis. These results imply independent evolutionary scenarios for the acquisition of their MK ability.